PENGARUH PEMBIAYAAN KREASI DALAM MENYALURKAN KREDIT USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP PEREKONOMIAN MASYARAKAT - Sawitri, Mega Nadila; Sutanty, Marisa (Jurnal Ekonomi & Bisnis, 2024)
This study aims to determine the effect of Kreasi Financing in distributing MSME credit to the community's economy. The type of this study was associative which aims to examine the effect of Kreasi Financing (X) on the Community Economy (Y). The type of data used was quantitative data collected directly by researchers from research respondents using a research instrument in the form of a questionnaire. The sample used in this study was all customers of Kreasi Financing at PT. Pegadaian (Persero) UPC Labuhan Badas, totaling 52 people who were selected using probability sampling techniques with the simple random sampling method. The data was processed using the Statistical Package for The Social Science (SPSS) application to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t-test), and determination coefficient testing (R2). The results of this study indicate that Kreasi Financing had a positive and significant effect on the community's economy. This means that the greater the amount of Kreasi Financing provided, the more the community's economy will increase. However, conversely, the lower the amount of creative financing provided, the more the community's economy will decrease. The ability of Kreasi Financing variables to effect on community economic variables was 30.3%, while the remaining of 69.7% was effected by other variables outside this research model, such as capital accumulation, workforce growth, and the level of technology application.